ANALISIS LEADERSHIP STYLE KEPALA RUANG KEPERAWATAN RAWAT INAP DALAM UPAYA PENINGKATAN KINERJA PERAWAT DI RS PKU MUHAMMADIYAH BANTUL - Rahadian Syah, Deby Zulkarnain; Iskandar, Rahayu (Poltekkes Kemenkes Palembang, 2022)
Introduction: Nursing management is a special task that must be carried out by nursing managers to plan, organize, direct, and supervise existing resources, both human resources, tools, and funds, so that they can provide effective nursing services to patients, family, and society. As a nursing manager, you must have a leadership spirit to achieve organizational goals that have been determined through other people. Objective: to determine the relationship between the leadership style of the head of the nursing room and the performance of inpatient nurses. Methods: This research is a quantitative research type, using a cross sectional approach. The population of this study was the head of the treatment room and inpatient nurses at PKU Muhammadiyah Bantul Hospital, Yogyakarta Special Region. Bivariate data analysis research using the contingency coefficient test. Result: The leadership style perceived by the nurse to the head of the room is democratic. The nurse's performance is in the sufficient category. The results of the bivariate analysis showed a significant relationship between the leadership style of the head of the room and the performance of nurses with a p value of 0.000 with a close relationship in the strong category of 0.617. Conclusion: leadership style affects the performance of nurses in the inpatient room at PKU Muhammadiyah Bantul Hospital.